Metformin: A Reflection on My Journey as Antidiabetic Drug (GAIMS Journal of Medical Sciences, 2023)
Here is a reflection by Metformin on its metaphoric journey and evolution as an antidiabetic drug and further role it presumes to play in alleviating human sufferings.